On-line UV-C prototype for postharvest antifungal treatment of citrus fruits - Ibiza Mauri, Salvador; Montesinos-Herrero, Clara; Palou, Lluís; Adrados, Carlos M. (CIGR-AgEng, 2021)
Synthetic fungicides used for postharvest treatment of citrus fruits are considered by consumers as a risk to human health and environment and alternatives to these chemicals that leave no residue on fruit are increasingly demanded. UV-C light irradiation is a clean and safe technology that when applied at the right doses may induce fruit resistance to postharvest diseases, reducing the need for chemical treatments. The objective of present study was to evaluate the preventive effect of UV-C light treatments against citrus postharvest green mould caused by the pathogen Penicillium digitatum. For this purpose, ‘Lanelate’ oranges and ‘Ortanique’ mandarins were puncture-injured in one side of the equatorial zone, treated with UV-C light at doses of 2.5 or 5 kJ/m2 and held at 20ºC and 90% RH for 6 days before inoculation with P. digitatum at 103 or 104 spores/ml. Control fruit was inoculated but not treated. Four replicates of 10 fruit each were used for each treatment. A new UV-C reactor prototype was used for postharvest treatment of citrus fruits. This prototype was able to treat the fruit while rolling, therefore exposing the surface of the fruit more homogeneously to UV-C light. The reactor, assembled on a commercial 3-m long roller conveyor, consisted of three low pressure 55-W mercury-vapour lamps, mounted on an aluminium frame placed 16 cm above the conveyor belt. UV-C average power supplied by the lamps at 6 cm above the conveyor belt was 5 mW/cm2. In order to regulate the flow rate and thus the UV-C exposure dose, the speed of the conveyor belt was set to provide a treatment time from 25 s to 2 min, which yielded a UV-C light dose from 2.25 to 5 kJ/m2, respectively. The number of infected fruit (disease incidence) as well as the diameter of the lesion (disease severity) and the percentage of fruit showing sporulated lesions (pathogen sporulation) were assessed after 3 and 7 days of incubation at 20ºC. Green mould incidence on ‘Lanelate’ oranges treated with a UV-C dose of 5 kJ/m2 was 64 and 42% lower than on control fruit after 3 and 7 days of incubation, respectively. Pathogen sporulation was 70 and 45% lower than on control fruit after these incubation periods. Disease severity was not significantly affected by UV-C treatments. On ‘Ortanique’ mandarins, treatments with UV-C light at 2.5 kJ/m2 reduced green mould incidence by 56% compared to non-treated fruit after 7 days of incubation. However, disease incidence and pathogen sporulation on ‘Ortanique’ mandarins treated with UV-C light at 5 kJ/m2 were similar to those on control fruit. In this case, although no rind damage was observed at the naked eye, UV-C light application probably resulted on slight phytotoxicity that counteracted the resistance induction. It can be concluded from these experiments that the election of the right UV-C dose was essential for the suitability of the treatments.